2021
DOI: 10.1111/aogs.14236
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound vs routine care before instrumental vaginal delivery: A systematic review and meta‐analysis

Abstract: Introduction:The objective was to report the role of intrapartum ultrasound examination in affecting maternal and perinatal outcome in women undergoing instrumental vaginal delivery.Material and methods: MEDLINE, Embase, CINAHL, Google Scholar and ClinicalTrial. gov databases were searched. Inclusion criteria were randomized controlled trials comparing ultrasound assessment of fetal head position vs routine standard care (digital examination) before instrumental vaginal delivery (either vacuum or forceps).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In case that ITU became the standard clinical practice, it is possible that the rate of vaginal examinations, failed instruments, and even the rate of cesarean births could be reduced by studying the progression of labor with greater accuracy. So far, studies have failed to show these benefits, but no harm has been found either [18,[21][22][23]. In addition, it is an examination that is well accepted, harmless, and without contraindications [9].…”
Section: Discussionmentioning
confidence: 99%
“…In case that ITU became the standard clinical practice, it is possible that the rate of vaginal examinations, failed instruments, and even the rate of cesarean births could be reduced by studying the progression of labor with greater accuracy. So far, studies have failed to show these benefits, but no harm has been found either [18,[21][22][23]. In addition, it is an examination that is well accepted, harmless, and without contraindications [9].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 1463 women, compared with standard care, ultrasound assessment prior to instrumental vaginal delivery did not affect the caesarean section rate (p=0.805), the composite adverse maternal outcome (p=0.428), perineal lacerations (p=0.800), postpartum haemorrhage (p=0.303), shoulder dystocia (p=0.862), prolonged stay in hospital (p=0.059), and composite adverse neonatal outcome (p=0.400) 34 . There was no increased risk of abnormal Apgar score (p=0.882), umbilical artery pH of <7.2 (p=0.713), base excess of > -12 (p=0.742), admission to neonatal intensive care unit (p=0.879), or birth trauma (p=0.968).…”
Section: Intrapartum Ultrasoundmentioning
confidence: 96%
“…The risk of incorrect diagnosis of fetal head position was lower when ultrasonography was performed before instrumental delivery, with a relative risk of 0.16 (p<0.001). Although ultrasound examination was associated with a lower rate of incorrect diagnosis of fetal head position and station, it failed to translate to improvement of maternal or neonatal outcomes 34 .…”
Section: Intrapartum Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] During second stage, a proposed algorithm model using the concept of a "traffic light" by incorporating both clinical and sonographic parameters is useful to consider. [59][60][61] It may guide clinicians on their decision on the choice of assisted vaginal delivery and alert junior obstetricians to consider senior assistance prior to commencing delivery. Asynclitism is often underdiagnosed.…”
Section: The Second Stage Of Labormentioning
confidence: 99%